WOMEN POLITICS RESERVATION BILL IN INDIA - Chengte, Pralhad V (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India is the largest democratic country in the world, where the women folk constitute nearly half of its population. Though the constitution guarantees equality to women along with men, but in politics very few women were able to make a room for themselves due to various reasons. The aim of this article is to explain about the Women Reservation Bill in India, reasons for low level participation of women and suggest measures to improve the participation of women in politics. The representation of women is low not only in Parliament but also in state assemblies, urban and rural local bodies. Those women who are having political background and influence were able to get seats in elections, before elections all political parties are giving promises but in actual practice very few seats were allocate to women candidates. In the present day politics money, muscle power and mafia are playing important role and these circumstance women does not like to enter into this field.